Analisis Hasil Belajar Matematika Siswa Di SMK Negeri 1 Maumere - Nona Gorgonia Paba; Wahyuningsi Wahyuningsi; Erwin Prasetyo; Muhamad Epi Rusdin (AlphaMath : Journal of Mathematics Education, 2020)
Student learning outcomes are a measure of student success in the learning process in class, and this study aims to determine the quality of student learning outcomes and aspects that affect mathematics learning outcomes in the comparison of trigonometry in a right triangle based on cognitive shutter at SMK Negeri 1 Maumere. Type of qualitative research with qualitative descriptive methods. Research subjects were students of class X DPIB-2 with a total of 34 people. This study uses data collection techniques by giving test questions and interviews. The analysis technique used in this research is descriptive qualitative data reduction, data display, and verification. The results of this study indicate that the learning outcomes of students with a low criterion are sufficient, the criteria are very large in number, the criteria for high are many, very high criteria the number is lacking. While the aspects affecting student learning outcomes are internal aspects and external aspects, internal aspects include students lack of interest in learning, students lack of understanding, memory and numeracy skills, while the external aspect includes family attention and support for students to repeat the material given by the teacher at home.